The apple tart of hope - Fitzgerald, Sarah Moore, 1965- (New York : Holiday House, 2016)
Oscar Dunleavy, a teenager who used to make incredible apple tarts, has gone missing and everyone thinks he is dead, but Oscar's best friend Meg, and his little brother Stevie, try to figure out what happened to him and form a bond and learn about commitment and friendship.
"First published in Great Britain 2014 by Orion Children's Books."
Keywords: Missing children -- Fiction; Hope -- Fiction; Friendship -- Fiction